Prevalent anatase crystalline phase increases the cytotoxicity of biphasic titanium dioxide nanoparticles in mammalian cells - Skubalova, Zuzana; Michalkova, Hana; Michalek, Petr; Strmiska, Vladislav; Guran, Roman; Merlos Rodrigo, Miguel Angel; Castkova, Klara; Hynek, David; Pekarik, Vladimir; Zitka, Ondrej; Adam, Vojtech; Heger, Zbynek (Colloids and surfaces. B, Biointerfaces, 2019)
Nanoparticular form of titanium dioxide (TiO2 NPs) belongs to important industrial material. Despite being widely used, serious contradictions regarding biosafety of TiO2 NPs remain. We anticipate that such discrepancies could be due to a lack of understanding of a linkage between TiO2 NPs phase composition and cytotoxicity. Therefore, we synthesized two types of biphasic TiO2 NPs differing in an anatase-brookite phase composition. The study presents an array of in vitro data suggesting that TiO2 NPs with a prevailing anatase phase composition possess higher cytotoxicity compared to TiO2 NPs with an equal anatase-brookite crystallinity. This phenomenon was evidenced by significantly higher inhibition of metabolic activity and growth of epithelial and neuroblast-like cells. Moreover, anatase-prevailing TiO2 NPs tend to produce higher amount of reactive oxygen species resulting in DNA fragmentation. Further insights into the molecular aspects of cytotoxicity of anatase-prevailing TiO2 NPs were obtained by comparative proteomics delineating that TiO2 NPs deregulate expression of a variety of proteins and associated pathways. This inevitably results in a decreased cellular ability to detoxify reactive oxygen species and respond to various stress conditions. The study provides novel data that add another piece to the jigsaw of the relation between structural features of NPs and biosafety.
Keywords: Cell Survival; Oxidative Stress; reaktivní formy kyslíku; oxidační stres; Humans; Cytotoxicity; Proteomics; Oxidative stress; viabilita buněk; krystalografie rentgenová; epitelové buňky; Crystallography, X-Ray; lidé; kovové nanočástice; titan; Reactive Oxygen Species; Nanotoxicology; buněčné linie; Epithelial Cells; Titanium; Cell Line; nádorové buněčné linie; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Cell Line, Tumor; Metal Nanoparticles